Implementation Analysis of the Industrial Revolution 4.0 in The Electronic Industry - Eko Setiobudi (International Journal of Education, Information Technology, and Others, 2022)
Productivity, efficiency and added value are something that the industry continues to strive for to increase the competitiveness in the market. One of them is through the implementation of industry 4.0. This is also in line with the government's program in responding to technological and information developments through the launch of Making Indonesia 4.0. The same thing was also done by PT. Tridharma Kencana (TDK), an electronic equipment assembly service (EMS) company that has been established since 2002. The idea of ​​implementing industry 4.0 at PT. TDK was poured through a concept entitled Integrated Production System, as a roadmap for implementing industry 4.0 within the company. The research was conducted using a case study approach, which was an approach used to investigate and understand an event or problem that has occurred by collecting various kinds of information which was then processed to obtain a solution so that the problems revealed can be resolved, with an emphasis on a certain depth of analysis that was greater in-depth. The research subjects targeted in this research were; BOD, Production Department, Engineering Section, IT Section, Project Section, QC Section, Warehouse Section and Maintenance Section. The objects of this research were the stages of implementation, PIC, activities and programs, system integration, and the impact or results of the implementation of industry 4.0 in the company. Continuous improvement was a production methodology commonly used in many industries. No exception at PT. Tridharma Kencana, which had run through lean manufacturing and six sigma. The development of industry 4.0 also encouraged companies to implement it through the concept of the Integrated Production System (IPS). And the results were quite significant. This can be seen from several indicators that were used as measuring tools for implementation results, using five outcome indicators, namely productivity, downtime, NTF, scrap and use of labor. Where all indicators showed the positive results which lead to increased efficiency both in terms of cost and time, increased productivity or production output and increased industrial competitiveness. This was what then provided added value for the company so that it was better able to compete in the industrial world in Indonesia